Depression and associated factors among children of prisoners in Bandar Lampung Prison, Indonesia - Mutiara Putri Adisa; T A Larasati (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: Depression can be caused by several factors, such as genetics, psychosocial, personality, psychodynamics, failure, and cognitive. Another factor in the occurrence of depression in children is the lack of positive reinforcement and family support.Purpose: To explain the factors that influence depression in children who are convicts at class II special penitentiary for children in Bandar Lampung.Method: Quantitative cross sectional on 75 samples selected through the technique simple random sampling. The research used a questionnaire that was given directly to respondents. Data were analyzed univariate and bivariate with chi square.Results: Statistical test with chi square between age and the occurrence of depression were obtained p-value = 0.539 (p-value > α = 0.05), for family support with the occurrence of depression obtained p-value = 0.001 (p-value < α = 0.05), with value Odds Ratio (OR) of 20,769 indicates that respondents who did not receive family support had a 20.8 times risk of experiencing mild-significant depression compared to respondents who received family support, while the length of sentence with the occurrence of depression was obtained p-value = 1.000 (p-value > α = 0.05), and mechanism coping with the occurrence of depression is obtained p value = 0.014 (p-value < α = 0.05), with value Odds Ratio (OR) of 5,000 indicates a mechanism respondent coping maladaptive have a 5 times risk of experiencing mild-significant depression compared to mechanical respondents coping it's adaptive.Conclusion: There is no relationship between age and length of sentence and the occurrence of depression and there is a relationship between family support and mechanisms coping with the occurrence of depression in convicts at class II special penitentiary for children in Bandar Lampung.